AN ANALYSIS OF SPEECH ACTS IN THE EPISODE “THE STRESS EXPERT” OF JAY SHETTY’S PODCAST: A PRAGMATIC STUDY - Daniel Danada; Fitria Wulandari; Melissa Melissa (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study examines illocutionary acts in the episode “The Stress Expert” of Jay Shetty's podcast through a pragmatic approach. The study aims to identify the dominant types of illocutionary acts and explain their communicative functions in mental health discourse. The method used is descriptive qualitative. Data were obtained through listening and transcription techniques of relevant conversation segments in podcast episodes available on YouTube. Each utterance was classified based on illocutionary act categories and analyzed for its pragmatic function. The results showed three dominant types of speech acts, namely assertive, directive, and expressive. Assertive speech acts function to convey information and explanations about stress and psychological well-being. Directive speech acts serve to guide and encourage behavioral change in listeners. Expressive speech acts serve to build emotional closeness and interpersonal support. The combination of these three types of speech acts forms a layered communication strategy that combines education, persuasion, and empathy. This study contributes to the development of pragmatic studies in the realm of digital discourse and shows that podcasts serve as a means of social action in mental health communication.